Vascular endothelial growth factor and its soluble receptors VEGFR-1 and VEGFR-2 in the serum of patients with systemic lupus erythematosus - Ewa Robak; Anna Sysa-jedrzejewska; Tadeusz Robak (Hindawi Limited, 2003)
We investigated the serum concentration of vascular endothelial growth factor (VEGF) and its two soluble receptors, sVEGFR-1 and sVEGFR-2, in a group of 60 patients with systemic lupus erythematosus (SLE), and 20 healthy controls, using an enzyme-linked immunosorbent assay. We examined a possible association between serum levels of these proteins and certain clinical and laboratory parameters as well as SLE activity. VEGF, sVEGFR-1 and sVEGFR-2 were detectable in all patients with SLE and in all normal individuals. The VEGF level was higher in active SLE (mean, 300.8 pg/ml) than in inactive SLE (mean, 165.9 pg/ml) (P<0.05) or in the control group (mean, 124.7 pg/ml) (P<0.04). The highest sVEGFR-1 concentrations were also detected in active SLE patients (mean, 42.2 pg/ml) and the lowest in inactive disease (mean, 32.0 pg/ml) (P<0.01). In contrast, the levels of sVEGFR-2 were lower in SLE (mean, 12557.6 pg/ml) than in the control group (mean, 15025.3 pg/ml) (P<0.05). We found a positive correlation between sVEGFR-1 concentration and the SLE activity score ρ=0.375(P<0.004) and a negative, but statistically insignificant correlation between sVEGFR-2 and SLE activity (ρ=−0.190, P>0.05). Treatment with steroids and cytotoxic agents did not influence VEGF or its soluble receptors levels. In conclusion, in SLE patients the levels of VEGF and sVEGFR-1 are higher in patients with active SLE than in inactive disease or healthy persons. In contrast, the level of sVEGFR-2 is lower in active SLE than in inactive disease. The imbalance between VEGF and its soluble receptors may be important in SLE pathogenesis.